2019
DOI: 10.19184/jid.v20i2.8995
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil Composition of Rose Flowers from Karangpring Village Jember District Extracted by Distillation and Enfleurage

Abstract: Karangpring is one tourist destination villages in Jember district which is popular with beautiful large rose field areas. Therefore, this area grows to be a leading producer of rose flowers in Jember district. However, the bulky presence of these flowers made its price becomes lower in regular days. Local community only uses and sells these fresh flowers as the flower for funeral. The rose flower has a great potency to be explored as a source of rose essential oil production. To date, there is no previous res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Compared to previous reports, there were some differences in the chemical composition rates of rose oil. Oktavianawati et al reported that they detected only aliphatic hydrocarbons (100%) in three rose cultivars [ 13 ]. However, Babu et al reported that long-chain aliphatic hydrocarbons including nonadecane, heptadecane, 9-eicosene, and docosane accounted for about 21.23% of the volatiles, while alcohols made up as much as 68.13% of the total oil in the Himalayas rose [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to previous reports, there were some differences in the chemical composition rates of rose oil. Oktavianawati et al reported that they detected only aliphatic hydrocarbons (100%) in three rose cultivars [ 13 ]. However, Babu et al reported that long-chain aliphatic hydrocarbons including nonadecane, heptadecane, 9-eicosene, and docosane accounted for about 21.23% of the volatiles, while alcohols made up as much as 68.13% of the total oil in the Himalayas rose [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rose products are in high demand throughout the world. In particular, rose essential oils have wide applications in food, cosmetics, and pharmaceuticals [ 1 , 2 , 13 ]. Although there are about 18,000 rose cultivars, only a few of them are used for fragrance applications [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Oktavianawati also reported similar results that the yield value of roses obtained in Karangpring Village, Jember Regency was 0.06-0.07%. Even though the extract's yield value is higher than essential oil's yield value, the wound healing effect of rose flower extract was still quite good [23], [24].…”
Section: Discussionmentioning
confidence: 98%
“…Rosa canina L. and Rosa damascene Mill. The genus Rosa (family Rosaceae) includes about 200 species spread in the temperate and subtropical zones of the Northern hemisphere [16,17]. Years ago the essential oils of roses were used in the field of cosmetology as perfumery due to their aromatic (strong) fragrance, and rose essential oils have repotted market worth.…”
Section: Introductionmentioning
confidence: 99%